Pengaruh Sleep Hygiene Therapy Terhadap Kualitas Tidur Pasien Skizofrenia : Effect of Sleep Hygiene Therapy on Sleep Quality of Schizophrenic - Aldiansyah (Indonesian Scholar Journal of Nursing and Midwifery Science, 2021)
Introduction: Sleep hygiene therapy is a non- pharmacological therapy that can be done by nurses in providing nursing actions to schizophrenic patients. Methods: The design of this research is Pre-Experimental Design in the form of One-Group Pretest- Postest Design. The sampling technique used purposive sampling with a total of 15 respondents. Results: The results of the analysis showed that there were differences in the sleep quality of schizophrenic patients before and after sleep hygiene therapy which was indicated by the results of the Paired Sample T- Test analysis where the significance results were p value = 0.000 <0.05. Discussion: The results showed the influence of sleep hygiene therapy on the quality of sleep of schizophrenia patients in the Elang 1 and Elang 2 at Soeharto Heerdjan Mental Hospital, Jakarta 2020.